PERAN PANGLIMA LAOT DALAM MEWUJUDKAN KEBERLANJUTAN WISATA BAHARI DI PROVINSI ACEH - Taufik; Lailatussaadah (ASKETIK: JURNAL AGAMA DAN PERUBAHAN SOSIAL, 2020)
Tourism has become one of the sectors contributing to the country's economic growth. In order for tourism to be sustainable, community participation is needed in its management, one of them is the role of customary institutions. This qualitative study aims to categorizing the types of tourism in Aceh and analyze the roles and obstacles of "Panglima Laot"as a Traditional institution that has the authority regulate maritime affairs in local wisdom in Aceh Province. Data collection techniques such as interviews and documentation studies, in the form of collecting and analyzing from several relevant reports, data, articles and journals. The results showed that tourism in Aceh Province can be categorized as seven types, namely: religious tourism, indigenous and cultural tourism, historical tourism, nature tourism, marine tourism, pilgrimage tourism and culinary tourism. The role of “Panglima Laot” is very important in the sustainability of marine tourism in Aceh Province. Because this institution is a recognized and respected existence by the fishing community to regulate and implement marine customary law and other maritime affairs. However, in carrying out their duties there are various obstacles, including the development of human resource capacity, budget and regional boundaries. Therefore we need support from the government for the strengthening of the “Panglima Laot” Institution in managing marine tourism and maintaining the survival of marine ecosystems in Aceh Province.